2013
DOI: 10.1056/nejmoa1208809
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of Oral Combination Antiviral Therapy for Hepatitis C

Abstract: This preliminary study suggests that 12 weeks of therapy with a combination of a protease inhibitor, a nonnucleoside polymerase inhibitor, and ribavirin may be effective for treatment of HCV genotype 1 infection. (Funded by Abbott; ClinicalTrials.gov number, NCT01306617.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
190
0
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(200 citation statements)
references
References 17 publications
6
190
0
4
Order By: Relevance
“…Safer and more effective HCV regimens may improve the prognosis of C-HCC. [34][35][36] A previous study also revealed the improved prognosis of B-HCC over time. However, that study included patients treated with surgery, ablation therapies and TACE.…”
Section: Discussionmentioning
confidence: 88%
“…Safer and more effective HCV regimens may improve the prognosis of C-HCC. [34][35][36] A previous study also revealed the improved prognosis of B-HCC over time. However, that study included patients treated with surgery, ablation therapies and TACE.…”
Section: Discussionmentioning
confidence: 88%
“…Le progrès récent le plus marquant, et qui constitue la vraie révolution, est le développement de straté-gies thérapeutiques combinant des antiviraux directs (AVD) s'affranchissant de l'utilisation d'interféron pegylé combiné à la ribavirine et, ainsi, de ses effets secondaires propres [28][29][30]. Ces multithérapies orales ont l'avantage d'être mieux tolérées, d'autoriser une prise moindre de comprimés et de réduire la durée des traitements (24 à 12 semaines).…”
Section: Revuesunclassified
“…6 Likewise, in a small phase IIa exploratory study, ABT-450 (an HCV NS3 protease inhibitor) boosted with low-dose ritonavir, in addition to ABT-333 (a non-nucleoside NS5B polymerase inhibitor) and RBV, led to SVR12 rates of 93% to 95% in previously untreated patients with HCV genotype 1 infection. 13 Thus, as potency of the IFN-free regimen increased, so did virologic response.…”
Section: Discussionmentioning
confidence: 99%